Including accident information in automatic bicycle route planning for urban areas. - Singleton, Alex D.; Lewis, Daniel J. (Hindawi, 2011)
Between 2005 and 2007 there were 9071 traffic accidents involving bicycles within London and this paper demonstrates the utility of Geographic Information Systems as a tool for analysing and visualising these occurrences. Through linkage of these spatial locations to a street network dataset it was possible to create a variety of intelligence about the types of street infrastructure where accidents predominantly occur. Additionally, a network routing algorithm was adapted to account for the frequency of accidents within a series of proposed journeys. This pilot routing application compared the quickest route with an accident avoidance weighted route between a series of origins and destinations. The results demonstrated that the routes avoiding areas of high accident volume did not increase journey length significantly; however they did provide a safer route based on empirical evidence over the volume of accident locations.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Stadtverkehr; Verkehrsunfall; Unfallvermeidung; Routenplaner